An Approach for Cost-Efficient Grid Integration of Distributed Renewable Energy Sources. (December 2015) - Luhmann, Till; Wieben, Enno; Treydel, Riccardo; Stadler, Michael; Kumm, Thomas
ABSTRACT: We describe a specific approach to capacity management for distribution grids. Based on simulations, it has been found that by curtailing a maximum of 5% of the yearly energy production on a per-generator basis, distribution grid connection capacity can be doubled. We also present the setting and first results of a field test for validating the approach in a rural distribution grid in northern Germany.